Sustainable Construction: Optimization of Microbial Soil Stabilization for Enhanced Construction Materials - Shikabonga, Joseph; Lungu, Kelvin Agabu; Mwaba, Denis; Mubita, Charles; Mulenga, Michael N; Mwanaumo, Erastus (International Journal of Engineering and Management Research, 2025)
Microbially Induced Calcium Precipitation (MICP) has emerged as an effective and sustainable method for soil stabilization, utilizing microbial processes to enhance soil strength through calcium carbonate formation. This research explores the transformation of Mongu sand into a strong construction material using MICP, with a focus on optimizing urease activity, bacterial concentration, and cementation media. Given the scarcity of rock conglomerates in the region but the abundance of sand, this study provides innovative solutions to address this issue by improving and even transforming materials into more suitable forms for construction. MICP presents significant potential for infrastructure development in areas with limited access to conventional materials, with future efforts aimed at scaling the process for larger and more complex projects. The findings provide insights into the optimal parameters for material transformation, revealing that maintaining urease activity between 10-15 µmol urea hydrolyzed per minute per mg of protein and bacterial concentrations of 1.5 x 10⁸ CFU/mL results in a substantial improvement in compressive strength and durability—up to 475% higher than untreated sand. Additionally, the study underscores the effectiveness of Sporosarcina pasteurii in promoting calcium carbonate precipitation, further emphasizing MICP’s potential for soil stabilization and construction in resource-constrained regions.